La diversidad lingüística como condición de trabajo docente y recurso de enseñanza: el caso de una escuela unitaria en Oaxaca - Valeria Rebolledo; Elsie Rockwell (Les éditions de la Maison des sciences de l'Homme, 2018)
Linguistic diversity is a fundamental condition for bilingual teachers working in schools serving children who speak indigenous languages. In Mexico, these schools also tend to have multigrade classes with students of different ages and grade-levels. These conditions lead teachers to adopt and create practices and skills that take advantage of the linguistic and social heterogeneity of their groups. In this article, we analyze, in a one-room school in a village in Oaxaca, the everyday co-construction of patterns of communication between a bilingual teacher and his indigenous students. We examine the complexity and simultaneity of the uses of varieties of both Chinanteco and Spanish in the verbal interaction between the teachers and the students. The findings contrast with policies that assume a clear-cut distinction between languages used in multilingual classes. They also allow us to question the concept of the school form as a framework for understanding the working conditions of teachers in rural environments with students who speak different language varieties.